Principles and Rules of Literary Method in Quran Tafsir (In the Example of Amin Al-khuli) - Abdurrahmanov, Gafgaz (Scholarya Demo Journal of Ruby, 2021)
Muslim scholars have conducted and continue to conduct extensive research to comprehend the Quran since its revelation. Obviously, these studies were carried out in accordance with the social and cultural conditions of the relevant time period. Muslims’ backwardness in all areas, including politics, the military, and the economy, led to the emergence of certain reformist movements in Muslim geography in the nineteenth century, which challenged conventional Islamic philosophy, reinterpreted the religion in conformity with the times, and created a solid foundation for the dissemination of idea. Some Muslim poets and philosophers were particularly impressed by Europe’s achievements in literary critique during this time period. One of the primary concerns of Muslim reformers at the time was the critique of conventional Islamic philosophy and the reinterpretation of the religion in light of current events. Egyptian reformist scholar Amin al-Khuli emphasized the importance of Muslims changing their approach to the Quran as a solution to religious challenges. Muslims, he believes, must first understand that the Holy Quran is a literary text and then act accordingly. In other words, “The Holy Quran is a masterpiece of Arabic literature. Therefore, it is vital to approach the Quran first and foremost in terms of its literary impact.” Amin al-Khuli, who did not create an independent commentary book, established the principles and rules of literary interpretation of the Quran in numerous works, and later certain academics from that school attempted to use this method in their works. This article examines the works of Amin al-Khuli, the founder of the school of literary commentary, in order to discover the principles and regulations of the tafsir school.